Peluang dan Tantangan Dalam Membangun Green Startup Dalam Lingkungan Kampus UIN Sulthan Thaha Saifuddin Jambi - Raditya Firnando; Faliza Zaidina Fitria; Ana Nurhayati; Ririn; Amiatul Laila (Kampus Akademik Publiser, 2026)
Environmental pollution due to the increasing volume of waste, particularly household organic waste that has not been optimally utilized, poses a serious problem in Indonesia while simultaneously opening opportunities for the development of green startups within higher education institutions. This study aims to analyze the opportunities and challenges of developing green startups at UIN Sulthan Thaha Saifuddin Jambi through the utilization of organic waste, specifically orange peels and pineapple peels, into eco-enzyme based on the zero-waste concept. The research employs a descriptive qualitative approach using literature review techniques on scientific articles, official government documents, and data from the National Waste Management Information System (SIPSN). The data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that UIN Sulthan Thaha Saifuddin Jambi has significant opportunities to develop green startups, supported by the abundant availability of organic waste (food waste at 40.77%), the strategic role of universities as centers for education, research, and innovation, as well as alignment with the achievement of Sustainable Development Goals (SDGs) 8, 9, 12, and 13. However, the development of green startups still faces challenges, including low green entrepreneurship literacy, limited access to funding, suboptimal commercialization of research outputs, and weak pentahelix collaboration among universities, government, and industry. This study recommends strengthening the green entrepreneurship curriculum, optimizing campus business incubators, and expanding strategic partnerships to support the sustainability of the eco-enzyme-based green startup ecosystem within the campus environment.